Magnetic ordering in the layered oxyselenides Sr2CoO2Ag2Se2 and Ba2CoO2Ag2Se2 - Herkelrath, S; Blandy, J; Clarke, S (Elsevier, 2018)
The antiferromagnetic structures of Sr2CoO2Ag2Se2 and Ba2CoO2Ag2Se2 are solved using powder neutron diffraction. Both compounds adopt the same magnetic structure, based on a √2a × √2a × c expansion of the nuclear cell with magnetic space group PC42/n (86.72 in the Belov-Neronova-Smirnova notation). This structure is adopted as a result of nearest-neighbour antiferromagnetic interactions within the CoO2 planes. The refined long-range-ordered magnetic moments of Sr2CoO2Ag2Se2 and Ba2CoO2Ag2Se2 are 3.7(1) and 3.97(3) μB per Co ion respectively. The refined moments are significantly greater than the value predicted from just considering the spin (3 μB); this is attributed to a significant orbital contribution to the magnetic moment in an analogous manner to that previously observed for Sr2CoO2Cu2S2 and the values conform to a relationship between the shape of the distended CoO4Ch2 (Ch = S, Se) octahedron and the size of the ordered moment established for a series of related compounds.